Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation. Issue 17 (1st September 2020) - Zeng, Ting; Tang, Yan-Ran; Li, Bin; Tasneem, Shumaila; Yuan, Han-Wen; Jia, Yan-Zhe; Daniyal, Muhammad; Hussain, Nusrat; Wang, Wen-Miao; Zuo, Da-Lei; Gong, Li-Min; Liu, Bin; et al.
Abstract: Twenty-four compounds were isolated from the roots of Polygonatum cyrtonema Hua, including a new octopamine dimer, named trans -bis( N -feruloyl)octopamine (1) . The structure was established on the basis of spectroscopic and chemical methods. All the extracts and compounds were evaluated for cytotoxic and antioxidant activities by using MTT and chemiluminescence assay. The extracts showed activity against MCF-7 and HepG-2 cell lines from IC50 0.30 to 1.01 mg mL −1 . Compound 3 exhibited activity against HepG-2 cell lines with IC50 8.99 μM. Compound 7 exhibited activity against Hela cell lines with IC50 2.53 μM and BGC-823 cell lines with IC50 7.77 μM. Moreover, compound 7 showed antioxidant with IC50 12 µM compared to the positive control with IC50 77 µM. Compound 16 exhibited activity against HepG-2 cell lines with IC50 1.05 μM and MCF-7 cell lines with IC50 1.89 μM. These results indicated that this plant might be potential in natural medicine and healthy food. Graphical Abstract: